REPRESENTASI MASKULINITAS PADA KARAKTER PEREMPUAN DI FILM THE 355 (2022) - Bella Charina Putri; Muhammad Bayu Widagdo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Films can construct gender roles in society by conveying them through their characters. The film